PAYROLL ACCOUNTING SYSTEM DESIGN AND WAGE IN GEA CRAF YOGYAKARTA - Wardani, Mira Kurnia (Accounting, 2010)
The purpose of this study was to determine how the implementation of Wage and Payroll Accounting System that has been done during this craf Gea. It also made the design of accounting systems appropriate Payroll and Wage data is applied Gea Craf. Collection done is by the method of documentation, methods of interviewing and observation methods. Where in the method of documentation we do the recording and retrieval of data. The method of interview we conducted interviews in order to obtain information, testimony and statements from the leadership and employees involved in payroll and pengupahan.Hasil of data collection indicate that the payroll and accounting system at Gea craf wage is still very simple and lack the necessary documents and calendar notes Gea very craf vulnerable to fraud. And the need for payroll and accounting system design an appropriate wage to be applied in Gea craf. Keyword : Payroll, Accounting, Wage